The Effect Of Using "Numbered Heads" Technique On Students' Speaking Skill Viewed From Students' Anxiety (A Quasi Experimental Research of 8th Grade of SMP Muhammadiyah 10 Surakarta in the Academic Years 2016/2017) - Setyani, Ardita Dwi; , Dr. Maryadi, M.A; , Mauly Halwat Hikmat, Ph. D (2017)
The research objectives are (1) to find out whether students taught by using Numbered Heads Technique get better score on speaking skill of 8 grade students, (2) to find out whether Numbered Heads Technique reduces students' anxiety of 8 grade students. (3) to find out whether there is any correlation between speaking skill and students' anxiety in English speaking. This study is quasi-experimental research. The populations were 66 students and the samples were 46 students, they were 8B and 8C. The collecting data techniques were test and questionnaire. The data were analyzed by using significant analysis (T-Test) and Correlation Analysis (Pearson Correlation). The results of the research are (1) there is any significant difference between score post-test of 8B and 8C where sig. (2-tailed) (0.030) < 0.05, t account (2.249) > t table (2.02) with degree of freedom (df) 41. (2) Numbered Heads Technique can reduce students anxiety in speaking skill where t account (1.611) > t table (0.90) (1.397) with df 8 for low anxiety, t account (1.023) > ttable (0.80) (0.941) with df 4 for high anxiety. (3) There was significant and strong relationship between anxiety and speaking skill which was indicated by ry1 y2 = 0.609 and sig. (2-tailed) (0.004) < 0.05.